PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA ADOBE FLASH DI KELAS V SDN 14 GURUN LAWEH KOTA PADANG - Johani, Nazrey; Hamimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning Pancasila Education Using the Problem Based Learning (PBL) Model Assisted by Adobe Flash Media in Grade V of SDN 14 Gurun Laweh, Padang City. Undergraduate Thesis. Faculty of Education. Universitas Negeri Padang. This research was motivated by field conditions indicating low student learning outcomes in Pancasila Education. This situation occurred because teachers had not implemented varied learning models and students’ understanding of the learning material was still not optimal, resulting in low student participation during the learning process. Therefore, this study aimed to describe the improvement of students’ learning outcomes in Pancasila Education through the application of the Problem Based Learning (PBL) model assisted by Adobe Flash media in Grade V of SDN 14 Gurun Laweh, Padang City. This study employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The research was conducted in two cycles, namely Cycle I consisting of two meetings and Cycle II consisting of one meeting. Each cycle was implemented through four stages: planning, implementation, observation, and reflection. The research instruments included observation sheets, tests, and non-test instruments. The research subjects were the teacher and 24 Grade V students of SDN 14 Gurun Laweh, Padang City, consisting of 10 male students and 14 female students. The results showed improvements in several aspects. The teaching module increased from an average of 83.33% in Cycle I to 95.83% in Cycle II. Teacher activity improved from 82.14% to 96.42%. Student activity increased from 82.14% to 92.85%. Students’ learning outcomes also improved from an average score of 75.42% in Cycle I to 87.08% in Cycle II. Thus, it can be concluded that the implementation of the Problem Based Learning (PBL) model assisted by Adobe Flash media is effective in improving learning outcomes in Pancasila Education for Grade V students.